Mapping lifelong learning quality: a bibliometric study - Serhiy O. Semerikov; Iryna S. Mintii (Academy of Cognitive and Natural Sciences, 2020)
This study employs bibliometric analysis to investigate the landscape of research on lifelong learning quality. Examining 218 publications from 1969 to 2020, we explore trends, topics, and collaborative networks. Our analysis reveals a surge of interest post-2000, covering diverse domains. Through clustering keywords, we identify themes like continuing education and quality assurance. Collaboration patterns among authors, institutions, and countries are also illuminated. This study offers insights into the complex realm of lifelong learning quality, providing a foundation for further research.